Values, interests and power: the politics of integrating services. Issue 2 (10th April 2018) - Kaehne, Axel
Abstract : Purpose: Differences in professional values, organisational interests and access to resources are key issues to be addressed when integrating services. They are widely seen by service planners and commissioners to be matters of governance. However, they also inform critical debates in political science. In essence they revolve around the question of distribution, or (how to decide) who gets what. The purpose of this paper is to re-frame the subject of inter-organisational governance in integration by conceptualising it through the lens of three prominent politico-theoretical approaches: the liberal, the authoritarian and the radical-utopian. Design/methodology/approach: A discussion paper that proceeds by utilising political science terms of reference and applying it to a public management problem. Findings: All three theories provide particular insights into the way in which service planners and commissioners may think about the inescapable plurality of values and interests in integration programmes. Where the liberal perspective places particular emphasis on the purpose and utility of organisational autonomy and self-direction, the authoritarian model highlights the need to produce results within tight timescales. It also accords with the manner in which integration policy is normally implemented, top down. The radical-utopian model is built on the least realistic assumptions but offers researchers a useful framework to assess the rationale and effectiveness of value-based policy in integration programmes wherever robust inter-organisational structures fail to materialise. Originality/value: Whilst there has been significant research on how to conceptualise integration programmes, scholars have usually championed a public management approach. The potential insights of political thought have not been explored until now. The paper demonstrates that the wider conceptual framework of political theory has significant purchase in the field of integration studies and can help us understand the benefits and limitations of an interdisciplinary approach.